2,3,5-trimethylphenol oxidation over Co-based solid catalysts - Saux, Clara (2013)
2,3,5-Trimethylphenol (TMP) was oxidized with hydrogen peroxide employing cobalt based solid materials. K6[CoW12O40]·6H2O (CoW12) was probed as selective catalyst for the oxidation obtaining better results when it was supported over ZSM-5 zeolites (CoW12-ZSM-5). CoW12-ZSM-5 was found to be an efficient catalyst in the oxidation of TMP to 2,3,5-trimethylbenzoquinone (TMBQ) and 2,3,5-trimethylhydroquinone (TMHQ) under mild reaction conditions. Liquid phase reaction parameters were evaluated obtaining better results employing hydrogen peroxide as oxidant, with an oxidant/substrate molar ratio of 5, methanol as solvent and 60 °C as reaction temperature. An apparent activation energy of 94.19 kJ/mol was obtained.